BERITA KONFLIK DALAM HARIAN AMBON EKSPRES - Telly Muriany; Andi Alimuddin Unde (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2011)
Abstract The aim of this research is to know the factuality, the impartiality and the social impact of Harian Ambon Ekspress in Reporting conflict in Maluku. The analysis units in the research are the conflict report that served in Harian Ambon Ekspres in early 2008 until February 2009 period with types of SARA (clan, religion,race and groups), socio-cultural and politic Conflict Report. The result of the research indicate that, according to the factuality most of the report that served suitable to the facts that happen, this is because of the existence of the official confirmation source from the in service government and security apparatus at the conflict area. Otherwise, according the impartiality, the unbalance report service is dominant in Harian Ambon Ekspres journalistic practice, this is because of the un-existence of certain party confirmation as the conflict contestant and the cover both sides practice. Factual information presentation without journalistic ethnic limitation and partial report presentation has a negative impact and it is nonsupport in creating social and politic stability in the community around the conflict area.Abstrak penelitian ini bertujuan untuk mengetahui fakta, keadaan dan dampak social dari peliputan konflik di Maluku oleh Harian Ambon Ekspress. Unit analisis dalam penelitian ini adalah liputan konflik yang disajikan dalam Harian Ambon Ekspress pada awal 2008 sampai februari 2009 dintinjau dari aspek SARA(suku, Agama, Ras, dan Kelompok), Sosial budaya dan politik. Hasil penelitian ini mengidentifikasikan bahwa menurut dari hasil fakta, sebagian besar dari hasil liputan itu sesuai dengan fakta yang terjadi dilapangan. Hal ini disebabkan karena sumber informasi yang ada berasal dari petugas pemerintah dan aparatur keamanan yang ada di wilayah konflik. Akan tetapi dari sisi lain, ada pihak –pihak tertentu yang berkepentingan dalam peristiwa konflik menilai liputan Harian Ambon Ekspress tidak seimbang terutama dalam cover-both sides. Mereka menilai bahwa informasi yang disajikan kurang dibarengi dengan etika jurnalistik, dan liputan hanya dilakukan sepotong-sepotong sehingga bisa berdampak negatif dan cenderung tidak mendukung terwujudnya stabilitas sosial politik di wilayah konflik.